Expression of c‐Kit discriminates between two functionally distinct subsets of human type 2 innate lymphoid cells. Issue 6 (28th March 2019) - Hochdörfer, Thomas; Winkler, Carla; Pardali, Katerina; Mjösberg, Jenny
Abstract: Human type 2 innate lymphoid cells (ILC2) are the only ILC subset that shows heterogeneous expression of the SCF receptor c‐Kit (CD117). Despite its use as surface marker to distinguish ILC populations, its influence on ILC2 biology has not been investigated. Here, we show that c‐Kit expression of peripheral blood ILC distinguishes two functionally distinct ILC2 subsets (c‐Kit hi and c‐Kit lo ). When examined for their potential for functional plasticity we found that c‐Kit lo ILC2 displayed greater potential to produce type 2 cytokines, possibly representing fully mature and lineage committed ILC2. On the other hand, c‐Kit hi ILC2 coexpressed the ILC3‐marker and chemokine receptor CCR6 and were able to mount a significant IL‐17A response under ILC3‐promoting conditions. In addition, c‐Kit hi ILC2 produced higher levels of IFN‐γ than c‐Kit lo ILC2 under ILC1‐conditions. Although costimulation with SCF did not further influence ILC2 plasticity, it augmented type 2 cytokine production. We conclude that c‐Kit marks distinct subpopulations of ILC2, which has therapeutic implications for conditions in which ILC2 are involved, such as allergy and asthma. Abstract : The cytokine milieu influences ILC2 subpopulations differentially. C‐Kit hi ILC2 show strong cell plasticity toward ILC1‐ and ILC3‐like phenotypes, while also producing type 2 cytokines. C‐Kit lo ILC2 is prototypical ILC2 with pronounced type 2 cytokine production and weaker ILC1‐like phenotype than c‐Kit hi ILC2. SCF cotreatment augments type 2 cytokine production specifically.